Biofuel feedstocks: implications for sustainability and ecosystem services - Diop, El Hadji Habib Sy (Kansas State University, 2013)
Biofuel feedstocks such as grains and cellulose are gaining increased attention as part of the U.S. portfolio of solutions to address climate change and improve energy security. As the future of biofuels unfolds, major concerns are emerging, including the sustainability of the soil resource in bioenergy cropping system. With a clear understanding of the sustainability risks that exist within the agricultural soil resources, it is now essential to develop metrics that document the soil health as well as the total biomass production of different cropping system. We tested the effectiveness of eight bioenergy plant species grouped between annual and perennial crops. Our main objective was to determine the sustainability of bioenergy cropping systems. There was significantly greater soil structural stability plus greater root biomass under the perennial crops but greater aboveground biomass in the annual crop. Differences in soil carbon measured to 1.2 m were not significant between energy crops after five years. A transparent, unbiased method to identify possible change in soil characteristics under bioenergy cropping practice was offered. Our next metrics were soil aggregate stability and microbial community structure as indicators of soil ecosystem health and environmental stability. The effects 24 years of differing levels of residue and fertilizer inputs on soil aggregate stability, aggregate C and microbial community structure were evaluated. A native, undisturbed prairie site, located nearby was used as a reference in this study. The results showed that greater inputs of inorganic N and increased returns of crop residues did not cause a proportionately greater increase in SOC. The abundance of microbial parameters generally followed their potential carbon pool in cultivated soils but a strong mismatch was observed in the native prairie site. Our results showed for the first time a clear disconnect between decomposers and macroaggregates; highlighting the role of soil structure in protecting organic matter. Soil carbon sequestration is one of the mechanisms that have been proposed as temporary measure to mitigate global climate change. However, there was a particularly large risk of negative effects of mitigation measures related to the increased removal of crop residues from cropping systems for use in bioenergy, if this means that soil carbon is reduced. Effective measurement of soil C at the field scale requires an understanding of the spatial variability of soil C on a landscape scale. Recent technological advances in soil C measurement offer new opportunities in this area. Our surface measurements of soil C by near infrared spectroscopy (NIRS) provided a quick assessment of soil C and, soil C predicted by NIRS and measured by dry combustion laboratory measurements was correlated with and R-squared of 0.84.
Keywords: Biofuel feedstocks; Sustainability; Ecosystem services; Soil carbon; Crop residue management; Agronomy (0285)